TEMPORAL ANALYSIS OF THE PRESENT AND FUTURE CLIMATE OF THE LAGOS COASTAL ENVIRONMENT - Fasona, Mayowa J.; Soneye, A. S, Muyiolu, S. K; Otusanya O. O, Ogundipe, O. T.; Onuminya, T., Adekanmbi, O. H.; Adeonipekun, P. (UNILAG Journal of Medicine, Science and Technology, 2019)
The Lagos coastal environment, a very delicate assemblage of coastal ecosystems, lies in the tropical lowland forest zone of southwest Nigeria. This paper analyses the long-term present and future climatic trend over the Lagos coastal environment using historical station-measured rainfall and temperature data for Ikeja, Lagos Island and Ijebu Ode stations and modeled data from the CMIP3 archive. The results suggest that long term mean annual rainfall over the Lagos coastal environment decreased by about -1.75mm per yr-1 from 1892 to 2015 and much of this was caused by the drastic rainfall decline of about -13mm per yr-1 in the period 1961-1990. Standardized rainfall anomaly suggests more year to year variations in rainfall in the Lagos coastal environment than experienced for Nigeria generally. Mean maximum temperature suggests a warming by about 0.012oC per yr-1 from 1944 to 2015. The future climate suggests an increase of about 0.6mm per yr-1 from 2016 to 2079 and a temperature rise of about 3oC above the present in 100years under a business as usual scenario. The results have severe implications for the ecosystems of the Lagos coastal environment and urban flooding and heat-related health impacts in the Lagos megalopolis.